Новий латинський напис з Болгарії і деякі питання історії Таврики - Зубар, В.М. (Археологія, 1991)
У статті автор дає нову інтерпретацію латинського напису, знайденого при розкопках церкви у м. Преславі, і намагається пов’язати Боспорську війну, згадану у цьому епіграфічному документі, з конкретними подіями у Тавриці наприкінці II ст. В статье дается новая интерпретация латинского посвящения, обнаруженного при раскопках Дворцовой церкви в г. Преславе на территории Болгарии. В надписи, поставленной от лица, служившего в I Италийском легионе, упоминается Боспорская война, в которой участвовал дедикант, что позволяет считать этот памятник новым важным источником по древней истории Северного Причерноморья.
На основании анализа передвижений римских воинских подразделений на территории Нижней Мезии во второй половине II — начале III вв., автор приходит к заключению, что военнослужащие I Италийского легиона находились в Таврике с конца 60-х годов II в. до рубежа II—III вв. Следовательно, Боспорская война, о которой говорится в посвящении, может быть также отнесена к этому периоду. Ряд сравнительных материалов, а также эпиграфические памятники с территории Боспора, в которых упоминается не только о победах над скифами, но и об их подчинении около 193 г. боспорским царям, позволили автору связать Боспорскую войну, упомянутую в надписи из Преслава, с совместными действиями Савромата II и римских войск в Юго-Западном Крыму против поздних скифов. Именно для усиления римских войск на Боспор и были переброшены солдаты I Италийского легиона, среди которых был и дедикант. Если предложенная интерпретация надписи из Преслава верна, то ее можно рассматривать в качестве важного свидетельства об одном из аспектов римской политики в Северном Причерноморье, направленной на военно-политическое подчинение поздних скифов. A new interpretation of a Latin dedication found under excavations of the Palace church in the town of Preslav in the territory of Bulgaria is given in the paper. The inscription made on behalf of a person who served in the 1st Italian legion mentions the Bosporic wan in which the dedicant took part. This fact permits considering this relic a new important source on ancient history of the Black Sea area.
Basing on the analysis of dislocations of Roman military units in the territory of the Lower Mesia it the late 2nd-early '.3d cent, the author comes to a conclusion that military men of the 1st Italian legion were in Tavrika from late 60ies of the 2nd cent, till the boundary of the 2-3 cent. Thus, the Bosporic War which is mentioned in the dedication may be also attributed to that period. A series'of comparative materials as well as epigraphical relics from the Bosporic territory which mention not only the victories over Scythians but also about their subordination to Bosporic tzars in approximately 193 have permitted the author to connect the Bosporic war, mentioned in the inscription from Preslav, with mutual actions of Savromat II and the Roman forces in the South-West Crimea against Late Scythians. It is for reinforcing of the Roman forces the soldiers of the 1st Italian legion, the dedicant among them, were dislocated to Bospor. If the suggested interpretation of the Preslav inscription is correct, it may be considered an important evidence for one of aspects of the Roman policy in the North Black Sea area directed to military and political subordination of Late Scythians.